2021
DOI: 10.3389/fgene.2021.626158
|View full text |Cite
|
Sign up to set email alerts
|

lncSAMM50 Enhances Adipogenic Differentiation of Buffalo Adipocytes With No Effect on Its Host Gene

Abstract: Fat deposition is one of the most important traits that are mediated by a set of complex regulatory factors in meat animals. Several researches have revealed the significant role of long non-coding RNAs (lncRNAs) in fat deposition while the precise regulatory mechanism is still largely elusive. In this study, we investigated the lncRNA profiles of adipose and muscle tissues in buffalo by using the Illumina HiSeq 3000 platform. In total, 43,809 lncRNAs were finally identified based on the computer algorithm. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…lncRNAs are involved in a variety of bioregulatory processes, including muscle growth, fat deposition, and lipid metabolism [50]. For example, lncSAMM50 [51], lncRNA 1 [52] enhances adipocytes differentiation. We showed that interfering with LincRNA-MSTRG.673.2 inhibited intramuscular fat deposition.…”
Section: Disscussionmentioning
confidence: 99%
“…lncRNAs are involved in a variety of bioregulatory processes, including muscle growth, fat deposition, and lipid metabolism [50]. For example, lncSAMM50 [51], lncRNA 1 [52] enhances adipocytes differentiation. We showed that interfering with LincRNA-MSTRG.673.2 inhibited intramuscular fat deposition.…”
Section: Disscussionmentioning
confidence: 99%
“…EGFP uorescence was used to monitor infection e ciency. Adenoviral transductions were performed according to laboratory protocols described in previous studies [13].…”
Section: Adenovirus Production and Transductionmentioning
confidence: 99%
“…In addition, Ctcflos [124] operate by variable shearing and thus shearing out shorter Prdm16 isoform transcripts which participate in promoting white fat browning. Some lncRNAs promote or inhibit the expression of downstream genes such as adipogenic differentiation, but the molecular mechanism underlying the regulation of related downstream genes, such as PVT1, lncSAMM50, lncAK079912, lnc 2310069B03Rik, HOTAIR, Dreh, LIPE-AS1, and HoxA11-AS1 are not well understood [125][126][127][128][129][130][131][132][133].…”
Section: Regulates Downstream Genesmentioning
confidence: 99%